Two Drosophila melanogaster mutations block successive steps of de novo purine synthesis. - Henikoff, S (1986)
Drosophila melanogaster purine auxotrophs ade2(1) and ade3(1) have been characterized biochemically. The ade2(1) strain is deficient in the fourth step of the de novo purine synthetic pathway catalyzed by phosphoribosylglycinamidine synthase (phosphoribosylformylglycinamide amidotransferase). The ade3(1) strain is deficient in the previous step catalyzed by phosphoribosylglycinamide formyltransferase (GART). The mutation responsible for the slightly leaky ade3(1) phenotype was characterized further. First, the mutant GART polypeptide was found to be of normal size and present at normal levels. Second, the GART-encoding region of the mutant was cloned, inserted into a yeast-Escherichia coli shuttle vector, and used to transform mutant yeast. Transformants showed very slight in vivo activity when compared to wild type, verifying that the mutation is in the GART coding sequence. Lastly, the region of the gene encoding GART activity from mutant and inbred parental strain flies was completely sequenced. A single base transition was found, leading to the substitution of a serine for a highly conserved glycine. These two mutations provide examples of blocks in the de novo purine synthetic pathway in a whole animal.